2020
DOI: 10.1177/1120672120970404
|View full text |Cite
|
Sign up to set email alerts
|

Vitrectomy combined with subretinal injection of tissue plasminogen activator for successful treatment of massive subretinal hemorrhage

Abstract: Purpose: To evaluate the outcome of vitrectomy combined with a subretinal injection of tissue plasminogen activator (tPA) to treat a massive subretinal hemorrhage. Methods: The medical records of 11 eyes of 11 patients (seven men, four women, mean age; 74.5 ± 9.6 years) with a massive (>10 disc area) subretinal hemorrhage were reviewed. The patients were treated with vitrectomy combined with a subretinal injection of tPA with or without external drainage. Results: The mean baseline visual acuity was 2.10 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…Here, we observed the occurrence of VH, SMH, and RD as postoperative complications, which were also reported in previous studies [ 5 , 6 , 30 ]. Based on our surgical experience, two possible explanations were proposed for the occurrence of these complications.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Here, we observed the occurrence of VH, SMH, and RD as postoperative complications, which were also reported in previous studies [ 5 , 6 , 30 ]. Based on our surgical experience, two possible explanations were proposed for the occurrence of these complications.…”
Section: Discussionsupporting
confidence: 91%
“…To minimize retina damage and surgical complications, Kadonosono et al [31] used the 47-gauge (50 μm) microneedle in their surgical procedures. Saito-Uchida et al [5] reported SMH and/or VH recurrence rate of 73% in 11 eyes after subretinal injection of rt-PA using the TM system and 5 (45%) more surgeries were needed to manage these complications. Other studies reported that 9 (60%) of 15 eyes and 10 (41.6%) of 24 eyes required at least one additional surgery for managing the postoperative complications of SMH, VH, or RD [32,33].…”
Section: Complicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Liu et al [7] reported good results using a 30-gauge (30G) needle for external drainage of subretinal hemorrhages through a scleral tunnel during vitrectomy. Saito-Uchida et al [8] reported subretinal injection of tPA with a 38G needle in 11 cases of subretinal hemorrhage, and retinal reattachment was achieved in all eyes. Venkatesh et al [9] reported that 25G pars plana vitrectomy (PPV) was performed along with injection of vancomycin directly into the subretinal abscess in endogenous endophthalmitis using a 41G needle, which improved the visual acuity to 6/24.…”
Section: Dear Editormentioning
confidence: 99%